The Relationship Between Duration of Valproic Acid Use and Body Weight in Children with Epilepsy at Haji Hospital, Medan - Jefri Naldi; Azzura Ligo (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Epilepsy is a neurological disorder that is often experienced by children and requires long-term treatment, one of which is valproic acid. Although effective in controlling seizures, this drug often causes weight gain, which can affect patient compliance. The purpose of this study was to determine the factors of epilepsy and the relationship between the duration of valproic acid use with body weight and body mass index (BMI) in children with epilepsy at RSU Haji Medan. This quantitative study used a descriptive analytical design. This study aimed to analyze the relationship between the independent variable (duration of valproic acid use) and the dependent variable (body weight in children with epilepsy). This study was observational because the data were obtained through observation and measurement. The study sample consisted of 33 respondents. The results showed that of the 33 children with epilepsy at RSU Haji Medan, the majority were female (57.6%) and aged 1-5 years (45.45%). All respondents had been taking valproic acid for 6 months, with 93.9% experiencing an increase in body weight and body mass index (BMI). The most dominant risk factors for epilepsy were head injury (21.21%) and complications at birth (21.21%). A comparison of data before and after valproic acid consumption showed significant changes in children's weight, height, and BMI. The conclusion is that there is a relationship between the duration of valproic acid use and increased weight and BMI in children with epilepsy, with the main risk factors being head injury and birth complications. Routine monitoring by medical personnel and parents, as well as further research with larger samples and additional variables, is recommended.